Effect of different surface treatments and multimode adhesive application on the Weibull characteristics, wettability, surface topography and adhesion to CAD/CAM lithium disilicate ceramic - Karina Barbosa Souza; Dayanne Monielle Duarte Moura; Sarah Emille Gomes da Silva; Gabriela Monteiro de Araújo; Rafael de Almeida Spinelli Pinto; Fabíola Pessôa Pereira Leite; Mutlu Özcan; Rodrigo Othávio de Assunção e Souza
Abstract This paper aims to evaluate the effect of different surface treatments on surface topography, wettability, and shear bond strength of resin cement to glass ceramic. Methodology: For SBS test, 32 blocks (7x7x2 mm) of lithium disilicate were obtained and randomly divided into eight groups (four blocks per group) according to each surface treatment (HF 20 s, 60 s, 120 s + silanization/S or Scotch Bond Universal/ SBU) and the Monobond Etch & Prime - MEP application followed or not by SBU. On each treated surface ceramic block, up to four dual-curing resin cement cylinders were prepared and light-cured for 40s (N=120/n=15). The specimens were thermocycled (10,000 cycles, 5-55°C, 30 s) and the SBS test (50KgF, 0.5 mm/min) was performed. Furthermore, failure analysis, wettability, AFM, and SEM were carried out. SBS data (MPa) were analyzed using Student's t-test, two-way ANOVA, Tukey's test (5%) and Weibull's analysis. Results: For HF experimental groups, two-way ANOVA presented the factors "etching time" and "bonding agent" as significant (p<0.05). After silane application, the HF groups presented similar bond strength. SBU application compromised the SBS, except for 120s etching time (HF120sS: 23.39ᵃ±6.48 MPa; HF120sSBU: 18.76ᵃ±8.81MPa). For MEP groups, SBU application did not significantly affect the results (p=0.41). The MEP group presented the highest Weibull modulus (4.08A) and they were statistically different exclusively from the HF20sSBU (0.58B). Conclusion: The HF 20s, 60s, 120 s followed by silane, promoted similar resin-bond strength to ceramic and the SBU application after HF or MEP did not increase the SBS.